Natural light as a determinant of the identity of architectural space - Ozorhon, Ilker Fatih; Uraz, Turkan Ulusu (Journal of Architecture and Urbanism, 2014)
In this study, the effect of natural light on the architectural space quality was examined. Contribution of natural light in three different dimensions as the readability of the space, the effect of the space, and its aesthetical evaluation was taken into consideration and discussed in the given order. The study involves a review of the related architecture literature, various books, articles, essays, and opinions. The major objective of this research is to explain the place of natural light in architectural design and its different aspects through its functional and semantic dimensions in the space. In this respect, contributions of natural light to the identity of the space were examined based on three renowned Turkish architects and their significant works. The paper focuses on the contribution of natural light to the space, emphasizing its qualitative aspects; whereas its physical and measurable aspects are beyond the scope of the paper. The study demonstrates the importance of experiencing the space in terms of understanding the aspect of light that determines the space identity. It also stresses that buildings designed considering the use of natural light could turn out to be more original.